Terbentuknya Keterlekatan Sosial Petani Durian Pada Usaha Pertumbuhan Ekonomi Desa Pakis, Kecamatan Panti, Kabupaten Jember Dalam Bentuk Desa Wisata Durian - Yoga Parulian Panggabean; Wanda Aziza (Jurnal Manajemen Pariwisata dan Perhotelan, 2024)
Pakis Village is one of the areas in Jember Regency that has quite extensive plantation land and there are still many agricultural activities carried out by the community in their daily lives. The existence of ties between durian farmers, tourism managers, and pioneers of durian tourism villages will certainly lead to gradual interaction called embeddedness. Oversocialized arises due to a shared awareness in which durian farmers and managers both want to benefit from what they are trying to do as a form of meeting individual economic needs, while undersocialized arises due to the lack of interaction carried out by durian farmers and managers with pioneers during commodity buying and selling activities. The results of this study indicate the existence of oversocialized and undersocialized in Durian Tourism Pakis Village, Panti District, Jember Regency.